Functional Analysis of Malus halliana WRKY69 Transcription Factor (TF) Under Iron (Fe) Deficiency Stress - Hongjia Luo; Wenqing Liu; Xiaoya Wang; Yanxiu Wang (Current Issues in Molecular Biology, 2025)
Fe deficiency in apple trees can lead to leaf chlorosis and impede root development, resulting in significant alterations in signaling, metabolism, and genetic functions, which severely restricts fruit yield and quality. It is well established that WRKY transcription factors (TFs) are of vital significance in mediating plant responses to abiotic stress. Real-time quantitative fluorescence (RT-qPCR) analysis displayed that Fe deficiency stress can significantly induce WRKY69 TF gene expression. However, the potential mechanisms by which the WRKY69 gene involved in Fe deficiency stress remains to be investigated. To address this limitations, the WRKY69 gene (MD09G1235100) was successfully isolated from apple rootstock Malus halliana and performed both homologous and heterologous expression analyses in apple calli and tobacco to elucidate its functional role in response to Fe deficiency stress. The findings indicated that transgenic tobacco plants exhibited enhanced growth vigor and reduced chlorosis when subjected to Fe deficiency stress compared to the wild type (WT). Additionally, the apple calli that were overexpressed WRKY69 also exhibited superior growth and quality. Furthermore, the overexpression of the WRKY69 gene enhanced the ability of tobacco to Fe deficiency stress tolerance by stimulating the synthesis of photosynthetic pigments, increasing antioxidant enzyme activity, and facilitating Fe reduction. Additionally, it increased the resistance of apple calli to Fe deficiency stress by enhancing Fe reduction and elevating the activity of antioxidant enzymes. For example, under Fe deficiency stress, the proline (Pro) contents of the overexpression lines (OE-2, OE-5, OE-6) were 26.18 mg·g−1, 26.13 mg·g−1, and 26.27 mg·g−1, respectively, which were 16.98%, 16.76%, and 17.38% higher than the proline content of 22.38 mg·g−1 in the wild-type lines, respectively. To summarize, a functional analysis of tobacco plants and apple calli displayed that WRKY69 TF serves as a positive regulator under Fe deficiency stress, which provides candidate genetic resources for cultivating apple rootstocks or varieties with strong stress (Fe deficiency) resistance.